Design of a switching mode three phase inverter - Rahman, Tawfikur; Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn (The Institute of Electrical and Electronics Engineers, Inc., 2016)
The inverter is an electrical switching control device that can be converted from one source to another source like as DC to AC or AC to DC. An efficient three leg IGBT inverter has been designed for microgrid systems which are simulated by MATLAB2014a /Simulink. The inverter switches are controlled by a pulse controller, which mainly generates the switching gate pulse. The switching pulse controller consists of two level pulse width modulation (PWM), phase lock loop (PLL), DC voltage and current regulator and Uref generator. The inverter gate pulse has designed using the input reference voltage and current, output reference signal and a reference phase angle. The pulse signal precisely synchronized with the microgrid line frequency of zero crossing sampling and reduces the total losses in the inverter which is almost 50W. Two lowpass LC filters have been used in this inverter that reduces the switching loss. The design of the three-phase inverter has better performance compared to single phase; the overall conversion efficiency of the inverter is 97.62%.